Analysis of Entrepreneurship Sustainability in Individual SMEs (One-Man-Show) from A Triple Bottom Line (TBL) Perspective: Study in Depok City, Indonesia - Iing Hilman; Masydzulhak Djamil; Ahmad Badawi Saluy; Mafizatun Nurhayati (Management Analysis Journal, 2023)
This research analyzes the relationship between sustainability practices and business outcomes in small and medium enterprises (SMEs). Sustainability in the context of SMEs managed by the head of the family (a one-man show) is characterized by the ability of SMEs to survive and succeed in a dynamic, competitive, and challenging business environment. SMEs must adapt to the changing environment and take strategies to achieve a balance between the Triple Bottom Line, namely people, planet, and profit, reducing pollution and degrading resources in the long term. The purpose of this article is to comprehend the nature of the sustainability of SMEs managed by the family's head. The results of the analysis show that SMEs must be able to survive economic and social changes, engage in responsible and ethical business practices, use natural resources effectively and protect the environment, and provide high-quality products and services. The results of this paper are in the form of metrics to measure how well SMEs meet the needs of stakeholders. With this sustainability metric, SMEs can observe further using the theme of sustainable practices. Thematic network analysis looks into the following major topics: (1) environmental concern behavior; (2) image and reputation; (3) economic interests; (4) social; and (5) environment. This study also discusses the important implications for SMEs who want to improve performance based on the Triple Bottom Line Theory and business sustainability.